Weight Management Challenges in Nulliparous Women Being Overweight or Obese Due to Pregnancy: A Qualitative Study - Pooran Heidari; Reza Negarandeh; Shahzad Pashaeypoor (Shiraz University of Medical Sciences, 2023)
Background: Getting overweight after pregnancy is a common phenomenon and getting back topre-pregnancy weight in the postpartum period is a major concern for mothers. This study aimed toexplain the challenges in performing post-pregnancy weight-management behaviors in nulliparouswomen being overweight and obese due to pregnancy.Methods: The present qualitative study was conducted with the conventional qualitative contentanalysis method based on Granheim and Landman's approach from October to December in 2021. Inthis study, participants were 15 women who referred to comprehensive health service centers in Tehran,Iran; they were purposefully selected according to the inclusion criteria. Data were collected throughindividual, in-depth, and semi-structured face-to-face interviews and simultaneously analyzed usingthe MAXQ Data version 10 software.Results: The mean age of the participants was 25.93±3.21 years. Data analysis resulted in three maincategories: 1) failure to adhere to calorie-restricted diets, 2) inability to engage in physical activity, and3) lack of adequate social support.Conclusion: Women with obesity due to pregnancy face many challenges to improve their weightcontrolbehaviors. As such, improving healthy behaviors not only requires relevant stakeholders'commitment, but also demands women, their families and communities' intention to engage in healthybehaviors.